A review of the practice and achievements from 50 years of applying OR to agricultural systems in Britain - Audsley, Eric; Sandars, Daniel L. (Palgrave Journals: OR Insight, 2009)
This paper will survey how things have changed over nearly 50 years of operational research (OR) applied to agriculture. The first ‘OR group' was set up at the National Institute of Agricultural Engineering by Dan Boyce in 1969 and is now at Cranfield University. It will examine how, and what, factors have influenced the type of work and the methods used. What applications have stood the test of time and what are just distant memories in paper publications? It will show that agricultural OR has moved on from its early beginnings in agriculture in applying OR techniques with simple analyses, to using and creating complex computer models. While it might be described as alive, it clearly needs to identify itself and its specific contribution to analysing decisions, to set it apart from the ‘anyone can simulate and optimize using a computer'. The skill of holistic systems modelling of combinations of processes at the decision-maker level is as important as the ability to use techniques.
Keynote conference paper at the 50th anniversary conference of the Operational Research Society that was subsequently published as a paper in OR Insight
Keywords: Agriculture; Review; Operational Research